Qandeel-e-adab: qawaid-o-insha class 1 - Saeed, Masood (Asian publishers Lahore, 2014)
"Qandeel-e-Adab: Qawaid-o-Insha Class 1" introduces young learners to the foundational principles of Urdu grammar and composition through engaging exercises and colorful illustrations, making learning fun and interactive. This book covers essential topics like alphabets, words, sentences, and basic writing skills, empowering young learners to express themselves effectively in Urdu.